Evaluating intraspecific variation in insect trait analysis. (22nd November 2020) - Gentile, Giorgio; Bonelli, Simona; Riva, Federico
Abstract : Intraspecific variation plays important roles in ecology and evolution. Yet, information on how species and populations vary remains scarce, particularly for insects and regarding functional traits. This lack of knowledge can be problematic in trait‐based ecology because traditional approaches assume negligible intraspecific variation, even for analyses that assess highly variable taxa. We measured 291 Arctic fritillary butterflies ( Boloria chariclea ) to assess the intraspecific variation in one population of this species, evaluating (i) how wingspan of Arctic fritillaries varies in relation to the other species of its community, and (ii) how well wingspan, a measure of body size, predicts weight, a measure of body mass. Wingspan of Arctic fritillaries varied between 2.62 and 4.07 cm, with the 95% interval range, including ∼33% (14/42) of the species in the community, and ∼30% (84/279) of the butterflies of Canada. The relationship between wingspan and weight was significant ( β wingspan  = 0.002, SE = 0.0008, P < 0.001), but relatively weak ( R 2 adj  = 0.31, F 2, 288  = 67.82, P < 0.001). We discuss our findings in relation to the assumption of species homogeneity and the use of proxies in the analysis of species traits, complementing our case study with simulations to illustrate how intraspecific and interspecific variation interact in determining when traditional trait analyses are robust. We suggest entomologists interested in trait analyses should critically evaluate how intraspecific variation could affect their inference, especially when evaluating species that are highly sexually dimorphic, phenotypically plastic, and/or distributed across broad environmental and spatial clines.